J. S. Bach’s Church Cantatas and Church Music Today - Peters, Mark A.; Tantra, Carolien Eunice (Sekolah Tinggi Teologi SAAT, 2021)
This article explores the church cantatas of German composer J.S. Bach (1685–1750) as models for how we can think about the practice of faithful worship in the Christian church today. The article begins with an overview of Bach’s vocation as a church musician, in which he served in various contexts throughout his life. The article focuses on Bach’s final calling as a church musician, as music director for the town of Leipzig for the final 27 years of his life. It explains the context of the main Sunday and feast day worship service in Leipzig, with particular attention to the role of the church cantata in this service. The article then presents a general overview of the characteristics of Bach’s church cantatas before exploring in-depth liturgy, text, and music in one particular example, Cantata 104, Du Hirte Israel, höre. It concludes by proposing that a study of J.S. Bach’s church cantatas can teach us lessons of three kinds—practical (how we do church music), creative (how we create art), and spiritual (for ourselves and our congregations)—that we can apply in our churches today.